2017
DOI: 10.1038/nrgastro.2017.136
|View full text |Cite
|
Sign up to set email alerts
|

Environmental triggers in IBD: a review of progress and evidence

Abstract: A number of environmental factors have been associated with the development of IBD. Alteration of the gut microbiota, or dysbiosis, is closely linked to initiation or progression of IBD, but whether dysbiosis is a primary or secondary event is unclear. Nevertheless, early-life events such as birth, breastfeeding and exposure to antibiotics, as well as later childhood events, are considered potential risk factors for IBD. Air pollution, a consequence of the progressive contamination of the environment by countl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
452
1
13

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 643 publications
(472 citation statements)
references
References 103 publications
6
452
1
13
Order By: Relevance
“…47,48 We performed a search of major electronic databases from inception to February 2018. The following databases were included: (1) Medline (Pubmed), (2) EMBASE, (3) Scopus and (4) Web of Science. Our search strategy included the following combinations: (1) 'Vitamin D' [and] 'Inflammatory Bowel Disease', (2) 'Vitamin D' [and] 'Ulcerative Colitis' and (3) 'Vitamin D' [and] 'Crohn's Disease'.…”
Section: Study Protocolmentioning
confidence: 99%
See 2 more Smart Citations
“…47,48 We performed a search of major electronic databases from inception to February 2018. The following databases were included: (1) Medline (Pubmed), (2) EMBASE, (3) Scopus and (4) Web of Science. Our search strategy included the following combinations: (1) 'Vitamin D' [and] 'Inflammatory Bowel Disease', (2) 'Vitamin D' [and] 'Ulcerative Colitis' and (3) 'Vitamin D' [and] 'Crohn's Disease'.…”
Section: Study Protocolmentioning
confidence: 99%
“…The incidence and prevalence of IBD is increasing worldwide and is associated with significant healthcare utilisation in the United States . Although the exact aetiology of IBD remains unclear, IBD is speculated to arise from a complex interaction between genetic susceptibility, derangements in immune homeostasis, inappropriate responses to gut microflora and various environmental triggers . Increasing evidence has proposed that vitamin D plays a protective role in the pathogenesis of inflammatory bowel disease .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have reported effects on the gastrointestinal tract [1,2] and with an increased risk for appendicitis, digestive tract cancers, and inflammatory bowel disease (IBD). Recent studies have reported effects on the gastrointestinal tract [1,2] and with an increased risk for appendicitis, digestive tract cancers, and inflammatory bowel disease (IBD).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the development of neurodegenerative diseases, such as Alzheimer's and Parkinson's disease, are also associated with microbiota dysbiosis, sex hormones levels, as well as perturbation of GH signaling . Interestingly, IBD is also strongly associated with AHR and the environmental pollutants known to activate it . Analogously, the ovarian development of Ahr KO mice presents similarities with PCOS models and the disease is associated with exposure to environmental pollutants .…”
Section: Disturbed Circadian Clock Gh and Sexual Development: An Unmentioning
confidence: 99%